Latinska epigrafija otoka Krka - Matijević-Sokol, Mirjana (2009)
Osim glagoljske epigrafije i spomenici s latinskim natpisima bili su područje Fučićeva interesa. Iako im nije posvetio više pozornosti u pisanim radovima, mnoge je rekognoscirao na terenu. U tom smislu ovaj prilog bit će posvećen latinskoj epigrafskoj baštini otoka Krka.
Besides Glagolitic epigraphy, monuments bearing Latin inscriptions were also an area of Fučić’ s interest. Although he did not dedicate much attention to them in his writings, he conducted a reconnaissance of many in the field. In this sense, this paper will be dedicated to the Latin epigraphic heritage of the island of Krk.
Projekt MZOS
Projekt MZOS
HRV